KESENJANGAN KEPUASAN PENGGUNAAN APLIKASI LINE DAN BLACKBERRY MESSENGER DI KALANGAN MAHASISWA ILMU KOMUNIKASI DI PEKANBARU - Syarifah Fathimy Azizah; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Developing of technology nowdays making interaction can be do with internet connection site such as social media. Line and blackberry messenger is application more used than other aplication in Indonesian. Purposes of this research is to know about sastifaction different when using Line and blackberry messenger application.This research using quantitative approach, the writter use unknown population totally sample to 96 respondents which are selected accidental sampling. To know how gratification discrepancy using comparative mean. The theory of Uses and Gratification, developed by Phillip Palmgreen is applied to analyze the result.The results of this research showed users application Line and blackberrry messenger obtained sastifaction different and results of comparative mean obtained GS Line 2,9638 and GS blackberry messenger 2,8805, results GO line 2,9419 and GO blackberry messenger 2,8100. Result gratification discrepancy line 0,0219 and blackberry messenger 0,07048 that means discrepancy blackberry messenger smaller than line. Line higher than blackberry messenger.Keywords: Gratification Discrepancy,gratification sought, gratification obtained, Line, blackberry messenger